Taxonomia e ecologia de parasitos metazoários de Metynnis cf. Lippincottianus de reservatórios em cascata da região neotropical - Gonçalves, Michelle Kalinka Carniel (2015)
The construction of reservoirs turns the lotic environment in still water, thereby altering the physical, chemical and biological conditions of the river. Several groups of organisms are studied in order to assess and minimize the impacts caused by these great buildings. As for the group of parasites of fish are found in the literature that analyze the parasites in isolated reservoirs, however little is known about the impact of these developments on the parasitic fauna. The objective of this thesis was to know how to behave parasites Metynnis cf. lippincottianus collected in the Tiete River and see how these parasites are organized in each of the collection environments, considering that each tank has different limnological and biological characteristics. Among the parasites collected were found four species new to science monogeneans described as Anacanthorus n. sp.1, Anacanthorus n. sp.2, Notozothecium n. sp.1 and Notozothecium n. sp.2. They were also collected Nematoda Spinoxyuris oxydoras and Procamallanus (Spirocamallanus) inopinatus and Digenea Ascocotyle sp. It can be seen that the abundance and richness of parasites increased depending on the distance from the point of greater pollution of the river Tiete, reflecting this way the environmental conditions of the collection sites. As the organization of the parasite community, it was observed that they follow a pattern of segregated organization. For being a fish sedentary, M. cf. lippincottianus performed as a host species with potential for parasites biomarkers studies. Considering the existence of reservoirs as inseparable components of the Brazilian landscape, this study contributed important data available to science about the parasitic fauna reservoirs of fish cascading Neotropics.